2022
DOI: 10.2196/34002
|View full text |Cite
|
Sign up to set email alerts
|

Brief Digital Interventions to Support the Psychological Well-being of NHS Staff During the COVID-19 Pandemic: 3-Arm Pilot Randomized Controlled Trial

Abstract: Background Health and social care staff are at high risk of experiencing adverse mental health (MH) outcomes during the COVID-19 pandemic. Hence, there is a need to prioritize and identify ways to effectively support their psychological well-being (PWB). Compared to traditional psychological interventions, digital psychological interventions are cost-effective treatment options that allow for large-scale dissemination and transcend social distancing, overcome rurality, and minimize clinician time. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 53 publications
(54 reference statements)
1
30
0
Order By: Relevance
“…Figure 1 presents the PRISMA flow diagram of the study review and selection process. Overall, 27 papers from 26 studies (2 papers reported aspects of the same study) met the inclusion criteria 26–52. Heterogeneity of study designs and the outcomes reported meant that it was not possible to synthesise the effects of each outcome.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Figure 1 presents the PRISMA flow diagram of the study review and selection process. Overall, 27 papers from 26 studies (2 papers reported aspects of the same study) met the inclusion criteria 26–52. Heterogeneity of study designs and the outcomes reported meant that it was not possible to synthesise the effects of each outcome.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies (22/26) related to the COVID-19 pandemic,29–33 35–522 related to influenza26 27 and 1 study to SARS28 and 1 to Ebola 34. A substantive number of interventions were premised on mitigating acute stress to prevent or minimise longer-term mental health problems.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations